Are different generations of female employees trapped by work-family conflicts? A study on the impact of family-supportive supervisor behavior on thriving at work - Zhao, Xiao; Zhang, Tian; Choi, Myeongcheol; Xu, Jingyi (Frontiers in Psychology, 2024)
Introduction With women's advancement in education and status, they drive corporate and social progress. However, traditional gender roles burden female employees with more family responsibilities, challenging work-life balance and affecting job performance. Organizations should supporting female employees to address these challenges. Thriving at work, a core aspect of positive work engagement, helps maintain enthusiasm and efficiency. This study explores the impact of family-supportive supervisor behavior (FSSB) on the thriving at work of female employees in China, considering generational differences in their work-family balance needs and the mediating mechanisms involved. Methods The methodology adopted in this study utilized Amos 26.0 and SPSS 25.0 to analyze data obtained from a sample of 279 female employees in China. Specifically, the study examined the direct impact of FSSB on thriving at work, alongside the mediating influence of work-family balance. Moreover, the research aimed to discern variations in these effects across different generational cohorts. Results This study highlights the direct impact of FSSB on female employees' thriving at work across different generational cohorts. Notably, the “post-90s” generation displayed the strongest direct effect of FSSB on thriving at work. Additionally, the impact of FSSB on work-family balance varied by generation, with the “post-90s” generation showing the weakest effect. Furthermore, the mediating role of work-family balance differed among generations, with complete mediation observed in the “post-80s” generation but no mediating effect in the “post-90s” generation, reflecting their distinct work-life balance priorities and needs. Discussion This study uses a generational difference perspective to explore the main and mediating effects of FSSB on thriving at work, enriching the theoretical research on generational differences and providing valuable insights for future research. Practically, organizations should focus on the needs of different generations while encouraging FSSB, fostering a supportive work environment and enhancing outcomes.